Ensaios sobre Tax avoidance, reputação corporativa e governança no Brasil - França, Robério Dantas de (2018)
This Doctoral thesis consists of three independent essays related to the effects of corporate governance and corporate reputation on tax avoidance of Brazilian companies. This thesis seeks to contribute to the tax avoidance debate based on the argument that Brazilian companies increase tax avoidance by highlighting fiscal risks, even in the presence of Corporate Governance and corporate reputation. Agency theory and Moral License Theory was used as theoretical basis. The first theory explains the agency conflict caused by the search for agent wealth to the detriment of owner wealth, as well as the use of governance as a reduce of this conflict, and the second theory to give an alternative explanation for the fact that some companies with strong corporate reputation to engage in aggressive tax avoidance, increasing the firm's fiscal risk. The First essay assumes that Brazilian private companies are prone to present a higher level of tax avoidance in relation to Brazilian publicly held companies. Regression models were estimated with random effects panel data and fixed effects with LSDV (Least Square Dummy Variables) to analyze the explanatory power of the variable of interest (private or public companies) in relation to the dependent variable (ETR), controlling by economic sectors and organizational life cycle (control variables) of 668 Brazilian firms from 2010 to 2015. The results indicate that: (i) Brazilian privately companies are prone to present lower ETRs in relation to publicly held companies; (ii) The stages of maturity and turbulence of the organizational life cycle are indirectly related to ETR. The Second essay advances in the tax avoidance analysis assuming that corporate reputation is a determinant of tax avoidance in Brazilian publicly held companies. The sample comprises 225 companies with 1,575 observations distributed in a panel data from the period (2010 to 2016). The estimations were made by panel data methods (RE, FE-LSDV, GLS, GLM, GHG and GMM) and resulting that Brazilian publicly held companies with an established corporate reputation increase their tax avoidance. This may indicate that the companies ignore possibility of fiscal risk and reputational damage which may arise, at least up to a certain level of tax aggressiveness. Finally, the Third essay assumes that managerial opportunism is encouraged by executive compensation and is mitigated by the presence of corporate governance and corporate reputation in Brazilian publicly held companies. Using GLS and GMM estimations for the determinants of tax avoidance (measured by BTD, NBTD and ABTD) it can be inferred that: (i) In an individual perspective of view, remuneration does not impact managerial opportunism; (ii) Corporate reputation can reduce managerial opportunism if analyzed individually. However, when considering its interaction with the variable remuneration there is an evidence in favor of incentives to managerial opportunism; (iii) In relation to corporate governance, the results were inconclusive when the governance variable is analyzed individually. However, when considering its interaction with the variable remuneration there is an evidence in favor of incentives to managerial opportunism.